Penerapan Microteaching terhadap Kesiapan Mengajar pada Mahasiswa Keguruan - Arni S.Aban; Roberta Bano; Maria Fatima Bouk; Maria Alexandria Mako; Adela Ursula Dahu Teti; Agustinus Molo; Fransiskus Tadeus Bau Bora; Damian Puling (Jurnal Pendidikan Dirgantara, 2025)
Microteaching is a small-scale teaching training method designed to enhance the pedagogical competence of prospective teachers before they enter the real educational environment. This study aims to analyze the role of microteaching in preparing teacher education students for actual teaching practice. The method used is a literature review combined with observation of microteaching implementation within the campus setting. The findings indicate that microteaching plays a significant role in improving fundamental teaching skills, such as mastery of subject matter, the use of appropriate teaching methods, classroom management, and effective communication abilities. In addition, microteaching contributes to building students’ self-confidence and mental readiness to face real classroom situations. Thus, microteaching has proven to be a strategic tool in shaping professional and classroom-ready future teachers.